2005
DOI: 10.3368/aoj.55.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Divergence Insufficiency

Abstract: The majority of patients were classified as primary divergence insufficiency. Though this form of divergence insufficiency is neurologically benign, it may easily mask a more severe neurologic condition for which the presenting symptom is also diplopia for distance viewing only. These results show the importance of obtaining a detailed history regarding the symptoms, as well as documenting neurologic signs, particularly nystagmus, when investigating divergence insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Horizontal ductions and versions should be normal. Christine Berscheid [ 9 ] showed that patients with secondary DI have the tendency to present with diplopia at a younger age than those with primary DI. The average age of patients with DI in the study was 51 years, compared with 62 years in patients with primary DI.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal ductions and versions should be normal. Christine Berscheid [ 9 ] showed that patients with secondary DI have the tendency to present with diplopia at a younger age than those with primary DI. The average age of patients with DI in the study was 51 years, compared with 62 years in patients with primary DI.…”
Section: Discussionmentioning
confidence: 99%
“…5,14 In 1954, Lyle 15 described how a lesion in the lower midbrain can mimic idiopathic divergence insufficiency but eventually progress to divergence paralysis with nystagmus. They have associated neurological signs, which include nystagmus, afferent pupillary defect, posterior ischemic optic neuropathy, skew deviation, vertigo, arm numbness, papilledema, facial paralysis, tremor, ataxia, and hemifacial spasm.…”
Section: ' Presentationmentioning
confidence: 99%
“…15 A retrospective study by Berscheid 14 in 2005 found that 21 of 44 patients with secondary divergence insufficiency either had nonspecific demyelinating disease (14) or multiple sclerosis (7). The patient was orthophoric at near, there was no nystagmus, and ocular movements were full.…”
Section: Secondary Divergence Insufficiencymentioning
confidence: 99%